Age-Related Changes in the Role of Social Motivation: Implications for Healthy Aging. (21st April 2021) - Isaacowitz, Derek M; Freund, Alexandra M; Mayr, Ulrich; Rothermund, Klaus; Tobler, Philippe N
Abstract: Prior research has established the importance of social relations and social embeddedness for motivation in healthy aging. Thus, social orientation appears to be essential for understanding healthy aging. This article focuses particularly on age-related changes in goals concerning social orientation, such as increased prioritization of emotional goals, increased prosociality/altruistic motives, generativity, and ego transcendence. We then consider open questions regarding gaps in the links between goals related to social orientation and healthy aging, as well as the implications of theories and research on social goals for leveraging motivation to promote healthy aging. In particular, interventions to promote healthy behavior in late life may be most effective when they match the themes of older adults' strivings to find meaning and purpose in their personal goals.